The Use of Digital Storytelling (DST) as an Effective Strategy for Enhancing Students’ Writing Skills: A Systematic Review - Syahregina Alyuvany; Dwiyani Pratiwi; Sunusi Dauda (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Digital storytelling (DST) refers to the merging of storytelling with digital media to address educational needs, such as communication, self-expression, and language acquisition, particularly writing skills. Writing has a significant role in students’ lifelong learning. Hence, teachers constantly seek novel ways to enhance students’ writing skills. To address the research question on describing the role of digital storytelling (DST) as an effective strategy in enhancing students’ writing skills and its opportunities and challenges, this paper provides a systematic review of several studies on Google Scholar and ERIC. The methodology employed in this paper was a Systematic Literature Review (SLR) with a qualitative approach, commonly referred to as meta-synthesis. The findings demonstrate that digital storytelling (DST) can be used as an effective strategy by teachers in enhancing students’ writing skills. Most of the authors of these research papers have presented empirical evidence supporting the benefits of integrating digital storytelling (DST) in the classroom to enhance students' writing more effectively.